Randomized Phase 3 Trial of Abiraterone Acetate in Men with Metastatic Castration-Resistant Prostate Cancer and No Prior Chemotherapy - Ryan, Charles J. (2012)
BACKGROUND: Abiraterone acetate, an androgen biosynthesis inhibitor, improves overall survival (OS) in metastatic castration-resistant prostate cancer (mCRPC) post-chemotherapy. Many mCRPC patients never receive chemotherapy and thus cannot benefit from abiraterone acetate; we evaluated this agent in mCRPC patients who had not received chemotherapy. METHODS: In this double-blind study, 1088 patients were randomized 1:1 to abiraterone acetate (1000 mg) plus prednisone (5 mg twice daily) or placebo plus prednisone. Co-primary end points were radiographic progression-free survival (rPFS) and OS. Secondary end points measured clinically relevant landmarks of mCRPC progression. Patient-reported outcomes included pain progression and quality of life. RESULTS: The study was unblinded after a planned interim analysis (IA) at 43% of OS events. Treatment with abiraterone acetate-prednisone resulted in a 57% reduction in the risk of radiographic progression or death (hazard ratio [HR], 0.43; 95% confidence interval [CI]: 0.35 to 0.52; P<0.001; 13% OS events IA) and an estimated 25% decrease in the risk of death (HR, 0.75; 95% CI: 0.61 to 0.93; P=0.009; 43% OS events IA). Secondary end points supported superiority of abiraterone acetate-prednisone: time to cytotoxic chemotherapy initiation, opiate use for cancer-related pain, prostate-specific antigen progression (all P<0.001) and performance status deterioration (P=0.005). Self-reported time to pain progression and patient functional status degradation favored abiraterone acetate-prednisone (P=0.05 and P=0.003). Grade 3/4 mineralocorticoid-related adverse events and liver function test abnormalities were more common with abiraterone acetate-prednisone. CONCLUSIONS: Abiraterone acetate produces OS and rPFS benefits, as well as significant delays in clinical deterioration and initiation of chemotherapy, in mCRPC.